Comparative Study of Efficacy of ORS with Paedicare (Ready to Use Solution) in Gastroenteritis in Children (Medical Forum Monthly, 2024)
Objective: To compare the efficacy of ORS with paedicare(Woodward’s England, ready to use solution) as oral rehydration therapy in children up to 10 years of age.Study Design: Randomized clinical trial.Place and Duration of Study: This study was conducted in Women Medical College affiliated teaching hospital in Abbottabad from 1 April 2014 to 1 October 2014.Materials and Methods: A sample of 100 patients suffering from dehydration was subjected to therapy. 50 of them were given ORS and 50 were given Paedicare (a ready to use oral electrolyte solution). The patients were kept under observation and results were noted.Results: out of the children treated with ORS 42 were successfully rehydrated within two days and 8 children took one week to recover while those treated with Paedicare 48 were rehydrated within two days and 2 children took one week to recover. Those children requiring more than two days recovering had associated illnesses like upper respiratory tract infection, otitis media and measles.Conclusion: Both ORS and Paedicare were effective in treating rehydration, Paedicare seem to be more hygienic, well constituted and had better results but ORS was less costly than Paedicare and has an edge over Paedicare especially among poor people.